THE INFLUENCE OF BRAND IMAGE, BRAND PERSONALITY AND BRAND AWARENESS ON CONSUMER PURCHASE INTENTION OF APPLE SMARTPHONE - Wijaya, Indriany M. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2013)
Intense competition in this globalization era has become a trigger in marketing and growing rapidly from year to year in technology industry. Smartphone is a new technology device of mobile phone that has become a part of people lifestyle today and has full functionally or more than just a usual mobile phone. The level of consumption trends of smartphone was held by segment of its brand. The consumers are likely to purchase products with the positive brand image or well known brands of products. This study was examining the influence of brand image, brand personality and brand awareness on consumer purchase intention of Apple Smartphone. The research conducted by using multiple regression analysis and collecting the data from questionnaire. The sample in this study is taken by 100 respondents of students at Faculty of Economic and Business Sam Ratulangi University in Manado. The result shows that brand image, brand personality and brand awareness has significantly influence on consumer purchase intention of Apple Smartphone. It was found that brand awareness is the variable that most has significantly influence on consumer purchase intention of Apple Smartphone than brand image and brand personality. Keywords: consumer, brand image, brand personality, brand awareness, and purchase intention